Lipomas: genetic basis of common skin lesions and their occurrence in rare diseases - Marzyńska, Dorota; Żaba, Ryszard; Lacka, Katarzyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Lipomas are usually sporadic, asymptomatic lesions, and their clinical and histologic presentation does not pose diagnostic difficulties. In ambiguous cases, however, knowledge of genetics is necessary. HMGA2 expression in adipose cells enables the differentiation of normal adipose tissue from lipoma and liposarcoma. Moreover, lipomas can be associated with genetic diseases, such as multiple endocrine neoplasia type 1, neurofibromatosis type 1, Wilson’s disease, or mitochondrial diseases. Lipomas can run in families (familial multiple lipomatosis) or be a part of genetic syndromes such as PTEN hamartoma tumor syndrome, Proteus syndrome, and Pai syndrome. This study aims to present the genetic basis of lipomas and diseases in which these lesions occur in the clinical picture.